(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The Federal Constitution of 1988, which opened the doors to the Brazilian Democratic State of Rights, demonstrates in its text, a true navigation chart for minorities, in defense of equality. However, at the same time, police speeches gained space in social relations, which ends up contributing to the dismay of the state of rights in the rigid prisoners. Prison requirements, in turn, are overly selective, predominantly segregating the excluded excluded. Thus, the present text has as its theme the Federal Constitution and the police state, delimiting the approach in prison selectivity. The research will be guided by the following question: to what extent can police discourse contribute to the dismay of the State of Rights in the universe of incarceration? To this end, we will try to bring, mainly, brief considerations about police discourse as a democratic regression, especially for minorities safeguarded by the Constitution; afterwards, considerations about the control society that takes exclusion as the key to obtaining security will be pointed out; finally, analyze the selectivity of prison requirements. The methodology adopted is the hypothetical deductive study, based on a bibliographic review, based on doctrines and legislation relevant to the matter.